Novel Insights into the Genetics and Pathophysiology of Adrenocortical Tumors - Drougat, Ludivine; Omeiri, Hanin; Lefèvre, Lucile; Ragazzon, Bruno (Frontiers in Endocrinology, 2015)
Adrenocortical tumors (ACT) are typically unilateral and can be classified as benign adrenocortical adenomas (ACA) or malignant adrenocortical cancers (ACC). In rare cases, tumors may occur in both adrenal glands as micronodular hyperplasia (primary pigmented nodular adrenal dysplasia, PPNAD) or as macronodular hyperplasia (primary bilateral macronodular adrenal hyperplasia, PBMAH). The study of certain tumor predisposition syndromes has improved our understanding of sporadic ACTs. Most ACAs are associated with abnormalities of the cAMP signaling pathway, whereas most ACCs are linked to alterations in IGF2, TP53 or the Wnt/βcatenin pathways. Over the past year, single-nucleotide polymorphism array technology and next-generation sequencing have identified novel genetic alterations in ACTs that shed new light on the molecular mechanisms of oncogenesis. Among these are somatic mutations of PKA catalytic subunit alpha gene (PRKACA) in ACA, germline and somatic mutations of armadillo repeat containing 5 gene (ARMC5) in PBMAH and somatic alterations of the E3 ubiquitin ligase gene ZNRF3 in ACC. This review focuses on the recent discoveries and their diagnostic, prognostic and therapeutic implications.